Atomically‐Precise Texturing of Hexagonal Boron Nitride Nanostripes (Adv. Sci. 17/2021). Issue 17 (8th September 2021) - Ali, Khadiza; Fernández, Laura; Kherelden, Mohammad A.; Makarova, Anna A.; Píš, Igor; Bondino, Federica; Lawrence, James; de Oteyza, Dimas G.; Usachov, Dmitry Yu.; Vyalikh, Denis V.; García de Abajo, F. Javier; El‐Fattah, Zakaria M. Abd; et al.
Abstract : Boron Nitride Nanostripes In article number 2101455, Khadiza Ali, J. Enrique Ortega, Frederik Schiller, and co‐workers explore a novel approach to nanopatterning a material with practical technological impact, namely growing hexagonal boron nitride (hBN) mono‐layers on vicinal surfaces. hBN forms a continuous atomically‐thin carpet on a curved rhodium (Rh) crystal, revealing a transformation from 2D to 1D electronic band structure at the Rh(337) orientation through electron scattering at N‐step‐Rh interface bonding points.